Respuesta :

Answer:

y = 3/4 or y = -3/5

Step-by-step explanation:

Solve for y:

(8 y - 6) (10 y + 6) = 0

Hint: | Find the roots of each term in the product separately.

Split into two equations:

8 y - 6 = 0 or 10 y + 6 = 0

Hint: | Look at the first equation: Factor the left hand side.

Factor constant terms from the left hand side:

2 (4 y - 3) = 0 or 10 y + 6 = 0

Hint: | Divide both sides by a constant to simplify the equation.

Divide both sides by 2:

4 y - 3 = 0 or 10 y + 6 = 0

Hint: | Isolate terms with y to the left hand side.

Add 3 to both sides:

4 y = 3 or 10 y + 6 = 0

Hint: | Solve for y.

Divide both sides by 4:

y = 3/4 or 10 y + 6 = 0

Hint: | Look at the second equation: Factor the left hand side.

Factor constant terms from the left hand side:

y = 3/4 or 2 (5 y + 3) = 0

Hint: | Divide both sides by a constant to simplify the equation.

Divide both sides by 2:

y = 3/4 or 5 y + 3 = 0

Hint: | Isolate terms with y to the left hand side.

Subtract 3 from both sides:

y = 3/4 or 5 y = -3

Hint: | Solve for y.

Divide both sides by 5:

Answer: y = 3/4 or y = -3/5